Uji Efektivitas Ekstrak Etanol Daun Mahoni (Swietenia mahagoni L.) Dalam Sediaan Losion Sebagai Repelan Terhadap Nyamuk Aedes aegypti - Anastasia Santaulina Putri Rosari; Endah Setyaningrum; Gina Dania Pratami; Endang Linirin Widiastuti (JURNAL BIOS LOGOS, 2024)
Preventive efforts made to avoid mosquito bites generally use repellants containing synthetic chemicals in the form of N, N-diethyl-meta-toluamide (DEET) and if used for a long period of time can cause damage to the human body. It is known that mahogany plants (Swietenia mahagoni L.) contain secondary metabolite compounds that have the potential as insect repellants. This study aims to determine the effectiveness of ethanol extract of mahogany leaves (S. mahagoni L.) in lotion as a mosquito repellent for Ae. aegypti, Effective Concentration 50% (EC50), physical properties and irritating effects of mahogany leaf ethanol extract lotion. This research was conducted in January 2024 - March 2024 at the Botany Laboratory and Zoology Laboratory, FMIPA, Unila. The study used a completely randomized design (CRD) with 4 treatments and 6 repetitions consisting of 4 levels of test concentrations, namely 0%, 5%, 10%, and 15%. The results of this study showed that the lotion of ethanol extract of mahogany leaves at a concentration of 15% had a protective power as a repellant of 87.63%, the EC50 value of the extract lotion at a concentration of 9,60%. The lotion has good physical properties and does not cause irritation on the skin. In conclusion, ethanol extract of mahogany leaves has effectiveness as a repellent for Aedes aegypti mosquitoes.